2020
DOI: 10.1049/hve.2019.0276
|View full text |Cite
|
Sign up to set email alerts
|

Commutation overshoots based on a novel model for series thyristors during the turn‐off process

Abstract: The commutation overshoot is an important reference index for the insulation coordination of the converter station as well as the thyristor voltage capacity. Although the dispersity of reverse recovery charges of series thyristors may affect commutation overshoots, especially those at the thyristor level, little literature has tried to analyse it in detail. Firstly, this study compares the turn‐off models of independent thyristor and elaborates their applicability to series thyristors. Then, a novel model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Numerous studies [7,8] have demonstrated that the primary cause of thyristor damage in pulse power applications occurs during the reverse recovery process. Therefore, researchers concentrate on addressing voltage distribution problems that arise from reverse recovery [9]. The reverse recovery characteristics of thyristors can be simplified or equivalently transformed based on ideal components to a certain extent, such as the SPICE model [10] and the Hu-Ki model [11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies [7,8] have demonstrated that the primary cause of thyristor damage in pulse power applications occurs during the reverse recovery process. Therefore, researchers concentrate on addressing voltage distribution problems that arise from reverse recovery [9]. The reverse recovery characteristics of thyristors can be simplified or equivalently transformed based on ideal components to a certain extent, such as the SPICE model [10] and the Hu-Ki model [11].…”
Section: Introductionmentioning
confidence: 99%
“…The use of detailed models becomes even more important when the number of switching devices in series rises [7]. For example, a trigonometric exponential model has been extended to consider also the stray inductances in [8], showing how the solution helps to better predict current and overvoltage of the device.…”
Section: Introductionmentioning
confidence: 99%